Synthesis of bis(thiosemicarbazone) derivatives: Definition, crystal structure, biological potential and computational analysis - Ates, D.; Gulcan, M.; Gumus, S.; Sekerci, M.; Ozdemir, S.; Sahin, E.; Colak, N. (Taylor & Francis Ltd, 2018)
(2-(2-(2-methoxyphenyl)hydrazono)cyclohexane-1,3-diylidene) bis(hydrazine carbothioamide) (L-1), 4-(2-(-2,-6-bis(2-carbamothioylhydrazono) cyclohexylidene) hydrazinyl)benzoic acid (L-2), and (2-(2-(4-bromophenyl) hydrazono) cyclohexane-1,3-diylidene) bis(hydrazinecarbothioamide) (L-3) bis(thiosemicarbazone) derivative compounds were synthesized by the condensation reaction of thiosemicarbazide and various ketone compounds. The structures of synthesized compounds were characterized by using FT-IR, H-1 and C-13-NMR spectra, elemental analysis and mass spectra. Also, the structure of L-1 has been determined by X-ray crystallographic analysis. Additionally, the antioxidant activities (free radical (DPPH) scavenging, iron chelating and reducing power) of compounds were evaluated. Especially, L-3 displayed good DPPH activity (84.13%) at 100mg/L. Moreover, pBR322 plasmid DNA cleavage activity was examined and all of the compounds were able to cleave the plasmid DNA. Finally, the ground state geometries of the thiosemicarbazone derivatives were optimized using Density Functional Theory applications at B3LYP/6-31G (d,p) level in order to obtain information about the 3D geometries and electronic structure.
Keywords: Thiosemicarbazone; crystal structure; antioxidant; DNA cleavage; computational analysis